Feature- and Face-Exchange illusions: new insights and applications for the study of the binding problem - Shapiro, Arthur G.; Caplovitz, Gideon P.; Dixon, Erica L. (Frontiers in Human Neuroscience, 2014)
The binding problem is a longstanding issue in vision science: i.e., how are humans able to maintain a relatively stable representation of objects and features even though the visual system processes many aspects of the world separately and in parallel? We previously investigated this issue with a variant of the bounce-pass paradigm, which consists of two rectangular bars moving in opposite directions; if the bars are identical and never overlap, the motion could equally be interpreted as bouncing or passing. Although bars of different colors should be seen as passing each other (since the colors provide more information about the bars’ paths), we found “Feature Exchange”: observers reported the paradoxical perception that the bars appear to bounce off of each other and exchange colors. Here we extend our previous findings with three demonstrations. “Peripheral Feature-Exchange” consists of two colored bars that physically bounce (they continually meet in the middle of the monitor and return to the sides). When viewed in the periphery, the bars appear to stream past each other even though this percept relies on the exchange of features and contradicts the information provided by the color of the bars. In “Face-Exchange” two different faces physically pass each other. When fixating centrally, observers typically report the perception of bouncing faces that swap features, indicating that the Feature Exchange effect can occur even with complex objects. In “Face-Go-Round,” one face repeatedly moves from left to right on the top of the monitor, and the other from right to left at the bottom of the monitor. Observers typically perceive the faces moving in a circle--a percept that contradicts information provided by the identity of the faces. We suggest that Feature Exchange and the paradigms used to elicit it can be useful for the investigation of the binding problem as well as other contemporary issues of interest to vision science.